Analysis of The Low Government Human Resource Governance on The Efficiency and Accountability of Public Services in Jambi City - Tia Nurjannah; Rahmatul Sa’diah; Suci Amelia; Herawati Ningsih; Zahratul Wilda (CV. Abhinaya Indo Group, 2025)
This study aims to analyze the poor governance of government human resources (HR) towards the efficiency and accountability of public services in Jambi City. The main problems identified are the unpreparedness of state civil servants (ASN) in adapting information technology and the weak work culture that is responsive to community needs. This study uses a descriptive qualitative approach, with data collection conducted through observation, in-depth interviews, and documentation. The study was conducted for three weeks, starting on April 2, 2025, involving two main informants: a civil servant from the Population and Civil Registration Office and a citizen who uses e-KTP services. The results show that the implementation of digital services such as the SIKESAL (Online Public Complaint Information System) application is still not optimal due to low digital literacy of ASN and minimal socialization to the community. In addition, e-KTP services are hampered by limited devices and data communication networks (Jarkomda), which causes the service process to be slow and inefficient. The impact is increased queues, delays in document issuance, and decreased public satisfaction and trust in public services. Based on indicators of productivity, service quality, responsiveness, responsibility, and accountability, it was found that the main weaknesses lie in the lack of technical competence of civil servants, unclear follow-up on complaints, and poor oversight of officer performance. These findings indicate that public service reform requires not only the provision of technology but also comprehensive and sustainable human resource capacity building. Therefore, a competency improvement strategy, an adaptive training system, and a consistent performance evaluation mechanism are needed to realize efficient, responsive, and accountable public services in Jambi City.